Low-temperature study of a new nevirapine pseudopolymorph - Silva, C. C. P. da (2007)
The title compound (systematic name: 11-cyclopropyl-4- methyl-5,11-dihydro-6H-dipyrido[3,2-b:20 ,30 -e][1,4]diazepin-6- one butanol 0.3-solvate), C15H14N4O 0.3C4H9OH, was crystallized in a new triclinic pseudopolymorphic form, a butanol solvate, and the crystal structure determined at 150 K. The molecular conformation of this new form differs from that reported previously, although the main intermolecular hydrogen-bond pattern remains the same. N—H O hydrogen bonds [N O = 2.957 (3) A˚ ] form centrosymmetric dimers and the crystal packing of this new pseudopolymorph generates infinite channels along the b axis.